Psoriasis Is Associated With Elevated Gut IL-1α and Intestinal Microbiome Alterations - Yegorov, Sergey; Babenko, Dmitriy; Kozhakhmetov, Samat; Akhmaltdinova, Lyudmila; Kadyrova, Irina; Nurgozhina, Ayaulym; Nurgaziyev, Madiyar; Good, Sara V.; Hortelano, Gonzalo H.; Yermekbayeva, Bakytgul; Kushugulova, Almagul (Frontiers in Immunology, 2020)
Background Psoriasis is a chronic inflammatory condition that predominantly affects the skin and is associated with extracutaneous disorders, such as inflammatory bowel disease and arthritis. Changes in gut immunology and microbiota are important drivers of proinflammatory disorders and could play a role in the pathogenesis of psoriasis. Therefore, we explored whether psoriasis in a Central Asian cohort is associated with alterations in select immunological markers and/or microbiota of the gut. Methods We undertook a case-control study of stool samples collected from outpatients, aged 30–45 years, of a dermatology clinic in Kazakhstan presenting with plaque, guttate, or palmoplantar psoriasis (n = 20), and age-sex matched subjects without psoriasis (n = 20). Stool supernatant was subjected to multiplex ELISA to assess the concentration of 47 cytokines and immunoglobulins and to 16S rRNA gene sequencing to characterize microbial diversity in both psoriasis participants and controls. Results The psoriasis group tended to have higher concentrations of most analytes in stool (29/47 = 61.7%) and gut IL-1α was significantly elevated (4.19-fold, p = 0.007) compared to controls. Levels of gut IL-1α in the psoriasis participants remained significantly unaltered up to 3 months after the first sampling (p = 0.430). Psoriasis was associated with alterations in gut Firmicutes, including elevated Faecalibacterium and decreased Oscillibacter and Roseburia abundance, but no association was observed between gut microbial diversity or Firmicutes/Bacteroidetes ratios and disease status. Conclusions Psoriasis may be associated with gut inflammation and dysbiosis. Studies are warranted to explore the use of gut microbiome-focused therapies in the management of psoriasis in this under-studied population.